PARTISIPASI PENDIDIKAN ISLAM DALAM MENETRALISIR ISU-ISU GLOBAL - Makbuloh, Deden (Analisis: Jurnal Studi Keislaman, 2013)
Globalization presents a paradox. On the one aspect shows the progress of science technology, but on the other aspect there are the threats  of a nation’s  morale. Main ideas in the  field of Islamic education in the era of globalization is the active participation  in organizing human needs in a comprehensive manner. In this context, dealing with competition Islamic education  are  locally, nationally,  and internationally.  Islamic education must still exist in yeast to give color and trend of globalization.  Therefore, Islamic education must be developed both theories, ideas and concrete action in the arena of globalization.  Global world may not  be denied, even just  to be faced with evidence of real performance. One of which is being used as Indonesian republican government policy is the implementation  of the curriculum in 2013. The curriculum is known as thematic integrative curriculum. However, among the thinkers and practitioners in education curriculum concept store is still a big question whether the issue will be resolved through the  Indonesian national  curriculum in 2013?  Answering this question needs a comprehensive review of the entire sub-system of education in Indonesia. Islamic education is an important part of a real existence in Indonesia from age to age. The existence of a real Islamic education is a real need to provide effect and active coloring toward the advancement of science and technology, as urged in the era of globalization.